2017
DOI: 10.1097/icl.0000000000000343
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Role for Inflammation in Contact Lens Discomfort?

Abstract: There have been only a few studies that have investigated a role for inflammation in contact lens-induced discomfort, and the strongest associations have been found with lipid degradation processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 187 publications
0
14
0
Order By: Relevance
“…4547 Inflammatory mediators released in tears have been recognized as one of the key components in ocular surface inflammation that have prominent roles in the pathophysiology of DED. 48 Of the multiple inflammatory biomarkers under investigation, cytokines and chemokines are the most frequently reported and studied in DED.…”
Section: Biomarkers Of Inflammationmentioning
confidence: 99%
See 2 more Smart Citations
“…4547 Inflammatory mediators released in tears have been recognized as one of the key components in ocular surface inflammation that have prominent roles in the pathophysiology of DED. 48 Of the multiple inflammatory biomarkers under investigation, cytokines and chemokines are the most frequently reported and studied in DED.…”
Section: Biomarkers Of Inflammationmentioning
confidence: 99%
“…48 Of the multiple inflammatory biomarkers under investigation, cytokines and chemokines are the most frequently reported and studied in DED. 4547 Components of lipid metabolism also have been reported to be correlated with clinical measures of DED, and include secretory phospholipase A2 (sPLA2), 49 prostaglandin E2 (PGE2), 50 arachidonic acid (AA), docosahexaenoic acid (DHA), eicosapentaenoic acid (EPA), and leukotriene B4 (LTB4). 51,52 Using a relatively new technology, isobaric tag for relative and absolute quantitation technology (iTRAQ) proteomics, tear proteins like α-enolase, α-1 acid glycoprotein 1, S100 A8/calgranulin A, S100 A9/calgranulin B, S100 A9/calgranulin B; S100 A4, and S100 A11 have been shown to be upregulated in DED tears.…”
Section: Biomarkers Of Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, it has been proposed that discomfort may arise as a result of the intrinsically sub‐clinical inflammatory response of the eye to contact lens wear . Preliminary studies have demonstrated a link between the mobilisation of inflammatory cells and contact lens‐induced discomfort.…”
Section: Preserving Ocular Healthmentioning
confidence: 99%
“…Currently, the role of inflammation in contact lens discomfort is controversial . A recent study that longitudinally evaluated Langerhans cells, being antigen‐presenting immune cells, in the cornea and conjunctiva demonstrated an initial transient increase in the density of these cells in people experiencing contact lens‐induced discomfort; the same effect was not observed in asymptomatic contact lens wearers, suggesting a potential inflammatory component to the aetiology of the condition …”
Section: The Process Of Assessing the Tear Film And Ocular Surface Inmentioning
confidence: 99%